2014
DOI: 10.5114/jcb.2014.43247
|View full text |Cite
|
Sign up to set email alerts
|

Non-melanoma skin cancer treated with HDR Valencia applicator: clinical outcomes

Abstract: PurposeRadiotherapy (RT) has played a significant role in treating non melanoma skin cancer (NMSC). High-dose-rate brachytherapy (HDR-BT) approaches have a paramount relevance due to their adaptability, patient protection, and variable dose fractionation schedules. Several innovative applicators have been introduced to the brachytherapy community. The Valencia applicator is a new superficial device that improves the dose distribution compared with the Leipzig applicator. The purpose of this work is to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(131 citation statements)
references
References 32 publications
7
124
0
Order By: Relevance
“…This is delivered twice weekly with a minimum interval of 48 hours. Tormo et al [10] also showed good toxicity results in patients treated in 6 or 7 fractions. Although most brachytherapy treatment schemas in the literature use 8 to 12 fractions [35,36,37,38,39,40], the fractionation used in this study does not result in a higher toxicity or a poorer cosmesis in comparison with a more fractionated treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is delivered twice weekly with a minimum interval of 48 hours. Tormo et al [10] also showed good toxicity results in patients treated in 6 or 7 fractions. Although most brachytherapy treatment schemas in the literature use 8 to 12 fractions [35,36,37,38,39,40], the fractionation used in this study does not result in a higher toxicity or a poorer cosmesis in comparison with a more fractionated treatment.…”
Section: Discussionmentioning
confidence: 94%
“…In radionuclide-based brachytherapy some applicators exist, which shield the radiation emitted by the 192 Ir source except for the region that needs to be irradiated. Among them, the Valencia applicators [10] were designed specifically to produce a collimated and homogeneous dose distribution within the patient's skin [33]. Compared to these applicators, EBT has the advantage of a shorter treatment time (2.5 minutes compared to 5 to 10 minutes), lower penumbra (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a median follow-up of 5.5 years, the local control rate was 98% (232/ 236). Similarly, Tormo et al reported a series of 32 NMSC patients treated with 42 Gy in 6-7 fractions using the Valencia applicator [53], with a 98% local control rate at around 4 years. The skin toxicity was all Grade 1, and resolved within 1-2 months.…”
Section: Hdr Brachytherapymentioning
confidence: 93%
“…Specific shielded applicators have been developed to focus the absorbed dose to the tumor volume, thus reducing absorbed dose to the surrounding healthy tissues. This is the case of the Valencia skin applicators (Nucletron, an Elekta company, Elekta AB, Stockholm, Sweden) [2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. They are tungsten cup shaped, in which the source has one single dwell position that incorporates a flattering filter providing a homogenous dose distribution at a given depth (see Figure 1).…”
Section: Purposementioning
confidence: 99%